Peace Governance and Multiculturalism: What role for Peace Education in the Balkans - Georgieva, Lidija (European Journal of Social Science Education and Research, 2019)
This article will focus on theoretical and practical dilemmas related to the concept of peace governance, and within this context on the possible transformative role of peace education trough facilitation of contact between communities in conflict. The basic assumption is that violent conflicts in the Balkans have been resolved trough negotiated settlements and peace agreements. Yet, education strategy including peace education and its impact on post-conflict peacebuilding and reconciliation are underestimated. Peace governance is recognized as a dynamic but challenging process often based on institutional and policy arrangements aimed to at least settle conflict dynamics or in some cases even to provide more sustainable peace after signing of negotiated settlement in multicultural societies. We will argue that education in general is one of the critical issues of peace governance arrangements that could facilitate peacebuilding and create a contact platform between communities. The first question addressed in this article is to what extend peace agreements refer to education as an issue and the second one relate to the question if education is included in peace agreement to what extent it contributes for contact between different conflicting communities. Although it is widely accepted that contacts between former adversaries contributes for multicultural dialogue it is less known or explained if and in what way peace agreements provisions on education facilitate contact and transformation of conflicting relations.